2018
DOI: 10.1155/2018/7343592
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Autonomic Nervous System, Saliva Cortisol Levels, and Cognitive Function in Major Depressive Disorder Patients

Abstract: Major depressive disorder (MDD) is associated with changes in autonomic nervous system (ANS) and cognitive impairment. Heart rate variability (HRV) and Pulse pressure (PP) parameters reflect influences of the sympathetic and parasympathetic nervous system. Cortisol exerts its greatest effect on the hippocampus, a brain area closely related to cognitive function. This study aims to examine the effect of HRV, PPG, salivary cortisol levels, and cognitive function in MDD patients by using noninvasive techniques. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 16 publications
1
12
1
Order By: Relevance
“…Likewise, FM and MDD share several common symptoms linked to the hypothalamic-pituitary-adrenal (HPA) axis and autonomic dysregulation systems for stress regulation, and their physiological markers are commonly found in FM and MDD 10,11. Cortisol and melatonin are two hormones that regulate the 24-hour pattern of bodily functions 12.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, FM and MDD share several common symptoms linked to the hypothalamic-pituitary-adrenal (HPA) axis and autonomic dysregulation systems for stress regulation, and their physiological markers are commonly found in FM and MDD 10,11. Cortisol and melatonin are two hormones that regulate the 24-hour pattern of bodily functions 12.…”
Section: Introductionmentioning
confidence: 99%
“…Unhealthy lifestyle may cause adverse vascular events after PCI [29]. Second, several studies have shown that depression may cause a dysregulation of the autonomic nervous system including low heart rate variability, high mean heart rate [30, 31]. Besides, the sympathetic nervous system can be continuously active without the antagonism of the parasympathetic nervous system in the context of depression, which may lead to the increase of pro-inflammatory cytokines and the decrease of anti-inflammatory cytokines, resulting in the state of inflammation [32, 33].…”
Section: Discussionmentioning
confidence: 99%
“…Both ANS divisions are highly coordinated in a dynamic sympathovagal balance aimed at maintaining physiological homeostasis. Disruption in ANS homeostasis, characterized by sympathetic overactivity and/or vagal underactivity, is an important contributor to adverse cardiac outcomes associated with depression [70,71]. Heart rate variability (HRV), that is, spontaneous oscillations of heart rate around its mean value, is determined by the dynamic interaction of the acceleratory sympathetic nervous system and deceleratory parasympathetic nervous system, indicating a healthy and adaptive organism.…”
Section: Role Of Autonomic Nervous System In Depressive Disordermentioning
confidence: 99%